250 Defining Developmentally High-Risk Full Term and Late Preterm Infants in the Neonatal Intensive Care Unit. (April 2022) - Carlton, Katherine; Cabacungan, Erwin; Cohen, Susan
Abstract : OBJECTIVES/GOALS: We aim to describe the preschool age developmental outcomes of children born full term or late preterm requiring care in the Childrens Wisconsin (CW) neonatal intensive care unit (NICU). Our objective is to develop a model to predict which NICU infants are at high risk for abnormal preschool age development based on their neonatal characteristics. METHODS/STUDY POPULATION: Retrospective cohort study including full term (â‰¥ 37 weeks) and late preterm (34-36 weeks) infants admitted to the CW NICU between 1/1/2013-12/31/2015 with a developmental assessment by a general practitioner or neuropsychology evaluation between 3-6 years of age. Data extraction will include maternal history, neonatal and delivery factors, and developmental evaluation results. Descriptive statistics will be used to determine the proportion of patients with abnormal preschool development stratified by NICU diagnoses, surgical procedures, subspecialty involvement, and patient demographics. Decision tree analysis will be performed to generate a prediction model identifying those infants at higher risk than their peers for an abnormal developmental assessment at 3-6 years of age. RESULTS/ANTICIPATED RESULTS: Analysis to date reveals 1360 patients â‰¥ 34 weeks gestation admitted to the CW NICU between 1/1/2013-12/31/2015. 80 patients received neuropsychology evaluations and the remaining 1280 patients had general practitioner developmental assessments. We anticipate that those infants referred for neuropsychology evaluation will have a higher proportion of abnormal developmental assessments when compared to those patients with routine general practitioner assessments. In addition, we hypothesize that common neonatal factors among the infants who received neuropsychology assessments will best predict abnormal preschool development within the decision tree analysis. DISCUSSION/SIGNIFICANCE: This study is one of the first to define risk factors in full term and late preterm infants cared for in the NICU associated with abnormal preschool age development. Identifying these infants at high-risk early on will allow providers to initiate early developmental interventions, schedule close NICU follow-up care, and provide parental counseling.